2017
DOI: 10.1038/s41598-017-12498-x
|View full text |Cite
|
Sign up to set email alerts
|

A dual targeted β-defensin and exome sequencing approach to identify, validate and functionally characterise genes associated with bull fertility

Abstract: Bovine fertility remains a critical issue underpinning the sustainability of the agricultural sector. Phenotypic records collected on >7,000 bulls used in artificial insemination (AI) were used to identify 160 reliable and divergently fertile bulls for a dual strategy of targeted sequencing (TS) of fertility-related β-defensin genes and whole exome sequencing (WES). A haplotype spanning multiple β-defensin genes and containing 94 SNPs was significantly associated with fertility and functional analysis confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 44 publications
(49 reference statements)
0
22
0
Order By: Relevance
“…Beyond standard genomic prediction, there is an additional desire to better understand the underlying biology of male fertility. While utilizing this technology to identify genes in the cattle industry is rare, a few examples include utilizing dual targeted β-defensin and exome sequencing to identify bull fertility genes in the dairy industry ( Whiston et al, 2017 ; Lyons et al, 2018 ). Genes identified have been found to be involved with spermatogenesis ( Whiston et al, 2017 ) and sperm binding ( Lyons et al, 2018 ).…”
Section: Genomic Predictionsmentioning
confidence: 99%
“…Beyond standard genomic prediction, there is an additional desire to better understand the underlying biology of male fertility. While utilizing this technology to identify genes in the cattle industry is rare, a few examples include utilizing dual targeted β-defensin and exome sequencing to identify bull fertility genes in the dairy industry ( Whiston et al, 2017 ; Lyons et al, 2018 ). Genes identified have been found to be involved with spermatogenesis ( Whiston et al, 2017 ) and sperm binding ( Lyons et al, 2018 ).…”
Section: Genomic Predictionsmentioning
confidence: 99%
“…Selective breeding is one strategy for improving bull fertility. Indeed, recent studies have identified and evaluated potential fertility-related biomarkers that could be used to select high fertility bulls [ 16 , 17 , 27 ]. It should be recognized that gene mapping studies have primarily focused on genetic variants with additive effects, whereas the role of non-additive effects has been largely overlooked.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, using a comparative genomic approach, two conserved spermatogenesis genes, MAP1B and PPP1R11 , were implicated in male fertility in Holsteins [ 12 ]. A recent study has identified novel genetic variants in both β-defensin and FOXJ3 genes related to bull sperm function [ 16 ]. Our group have identified regions in BTA21 and BTA25 strongly associated with service sire fertility in US Holstein bulls [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beta-defensin 126 increases the net negative charge on sperm (Tollner et al, 2012), increases sperm motility, mucus penetration in vitro (Fernandez-Fuertes et al, 2016) as well as sperm binding to oviductal epithelium in vitro (Lyons et al, 2018). We have also recently characterised the genetic variation in bovine β-defensin genes as well as completing the first whole-exome sequencing of AI bulls of divergent fertility (Whiston et al, 2017). This dual approach successfully identified novel variants in both beta-defensin and FOXJ3 genes as potentially regulating SCR through differential oviductal binding ability, as assessed in vitro (Whiston et al, 2017).…”
Section: Sperm Communication and Interaction With The Female Tractmentioning
confidence: 99%
“…We have also recently characterised the genetic variation in bovine β-defensin genes as well as completing the first whole-exome sequencing of AI bulls of divergent fertility (Whiston et al, 2017). This dual approach successfully identified novel variants in both beta-defensin and FOXJ3 genes as potentially regulating SCR through differential oviductal binding ability, as assessed in vitro (Whiston et al, 2017). Using a microarray-based approach, Legare et al (2017) characterised the expression of genes along the caput, corpus and cauda epididymis in bulls which differed in SCR.…”
Section: Sperm Communication and Interaction With The Female Tractmentioning
confidence: 99%